STARBUCK EXPANSION IN DEVELOPING COFFEE BUSINESS IN INDONESIA IN 2013-2017 - Robby "; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research tells about "starbuck expansion in developing coffee business in indonesia in 2013-2017. Coffee is one of the large trading commodities. The amount of Indonesian coffee consumption is very high. Starbucks company is one of the multinational companies from USA which is engaged in the coffee shop, Starbucks is expanding its business into Indonesia.This research uses descriptive explanative method, with library data collection techniques through books and the internet. The perspective used is Neoliberalism by Adam Smith. The level of interest group analysis by Euegene J. Kolb. The theory used is the investment theory by Harry Markowitz.The results of this study are the expansion of Starbucks in Indonesia experiencing fluctuations in the number of outlets, profits, income, sales, from 2013 and 2017, and starbuck corpooration was implemanting the canvas business model in indonesia Keywords : expansion, business, coffee, import, neoliberalism, investation